Who am I as a Sexual Being? The Role of Sexual Self-Concept Between Dispositional Mindfulness and Sexual Satisfaction among Child Sexual Abuse Survivors - Guyon, Roxanne (Journal of interpersonal violence, 2023)
Childhood sexual abuse (CSA) is associated with long-lasting and pervasive impacts on survivors’ sexual health, particularly on their sexual satisfaction. Dispositional mindfulness has been found to be associated with greater sexual satisfaction among adult CSA survivors. However, the mechanisms involved in this association remain understudied. The present study examined the role of sexual self-concept (i.e., sexual esteem, sexual preoccupation, and sexual depression) in the relationship between dispositional mindfulness and sexual satisfaction among CSA survivors. A total of 176 adult CSA survivors (60.6% women, 39.4% men) completed an online survey assessing dispositional mindfulness, sexual self-concept, and sexual satisfaction. Path analyses revealed that dispositional mindfulness was positively related to sexual satisfaction through a significant indirect effect of higher sexual esteem and lower sexual depression. The integrative model explained 66.5% of the variance in sexual satisfaction. These findings highlight the key roles that dispositional mindfulness and sexual self-concept play in CSA survivors’ sexual satisfaction. Implications for interventions based on trauma-sensitive mindfulness targeting the sexual self-concept are discussed, as they may promote sexual satisfaction in adult CSA survivors.